Comparative analysis of benzodiazepines during the Covid-19 pandemic sales by a drug distributor in a city in the interior Bahia (Research, Society and Development, 2022)
Social isolation, resulting from the Covid-19 pandemic, was one of the main measures to contain the virus, which soon proved to be unsustainable, causing social and economic problems, stressors that historically worsen negative psychological effects such as anxiety and depression, raising the demand for anxiolytics, especially benzodiazepines, one of the main groups used to treat psychological problems, but with many side effects and risk of dependence. This study carried out a comparative analysis of the sales of benzodiazepines during the Covid-19 pandemic by a drug distributor in a city in the interior of Bahia. This is a retrospective and descriptive research with a quantitative approach, carried out in a city in the interior of Bahia, through a drug distributor operating throughout the state. The sample consisted of the main benzodiazepines marketed in Brazil in the years 2019, 2020 and 2021. The analyzed data were transformed into graphs and tables for better visualization, aiming to contextualize and discuss them, in order to verify which drugs of the class had the highest outputs and the variations in sales in the face of the pandemic scenario. The results showed a significant growth in the commercialization of benzodiazepines in 2020 and a slight decline in 2021. As they are products that pose risks to physical and mental health, a deeper approach by prescribing physicians is necessary regarding the possible risks of the indiscriminate and improper use of this drug class.